2015
DOI: 10.18488/journal.ar/2015.2.3/101.3.68.75
|View full text |Cite
|
Sign up to set email alerts
|

Stover Yield and Chemical Composition in Some Sorghum Varieties in Gadarif State, Sudan

Abstract: An experiment was conducted at the faculty of Agricultural and Environmental Sciences farm, University Contribution/ OriginalityThis study is one of very few studies which have investigated the nutritive value and dry matter yield of local sorghum varieties in Gadarif State, the most important region for sorghum production in Sudan. It contributes to the existing literature in the analysis of correlation between morphological traits and dry matter yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…It was observed significant differences among the crops and their interaction with environment regarding yield and quality properties However, variations have been also observed in different agronomic and quality were also noted by Barutcular et al (2016a, b, c;Akdeniz et al, 2018b;Yıldırım et al,2018). The variability in NDF, ADF, cellulose and lignin concentrations of sorghum stover in different species has been reported earlier (Hamed et al, 2015) and it is reported that forage with high NDF levels had higher concentrations of the CB2 fraction, which is more slowly degraded in the rumen, impacting microbial synthesis and animal performance (Ribeiro et al, 2001). Carvalho et al (2007) reported that NDF concentration influences carbohydrate fraction CB2 and forages high in NDF concentration usually have higher values of CB2.…”
Section: Crude Protein Crude Ash Oil Content Ndf Adf and Cellulosementioning
confidence: 67%
“…It was observed significant differences among the crops and their interaction with environment regarding yield and quality properties However, variations have been also observed in different agronomic and quality were also noted by Barutcular et al (2016a, b, c;Akdeniz et al, 2018b;Yıldırım et al,2018). The variability in NDF, ADF, cellulose and lignin concentrations of sorghum stover in different species has been reported earlier (Hamed et al, 2015) and it is reported that forage with high NDF levels had higher concentrations of the CB2 fraction, which is more slowly degraded in the rumen, impacting microbial synthesis and animal performance (Ribeiro et al, 2001). Carvalho et al (2007) reported that NDF concentration influences carbohydrate fraction CB2 and forages high in NDF concentration usually have higher values of CB2.…”
Section: Crude Protein Crude Ash Oil Content Ndf Adf and Cellulosementioning
confidence: 67%
“…Sorghum (Sorghum bicolour (L.) Moench) is an important crop in Sudan, and the country ranked eighth in the world in sorghum grain production (3.5 million tonnes) in 2014 (Hamed et al 2015). Jiménez et al (1993) studied the application of sorghum stalks in pulp and papermaking and determined they had better properties than other agricultural residues, such as olive tree fellings, wheat straw, sunflower stalks, vine shoots, and cotton plant stalks.…”
Section: Introductionmentioning
confidence: 99%